(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract Target costing and cleaner production are among the most important techniques in the field of cost and management accounting, which, when integrated, enable economic units to achieve the goal of cost management by reducing it by calculating cost more accurately than traditional methods.To achieve this, the researcher relied on the inductive approach in writing the theoretical framework for the research, relying on foreign and Arabic books, dissertations and university theses, foreign and Arabic research and periodicals related to the subject of the research, and relying on the descriptive and analytical approach in the aspect of applied research based on a set of means such as financial data, personal interviews and field visits. Fayd Al-Qassim Metal Industries Company, and the cooling product was chosen, which is one of the products of Fayd Al-Qassim Metal Industries Company, with the aim of improving its quality and enhancing its competitive position compared to similar products in the local markets and converting it from a traditional product to an environmentally friendly product in addition to the low cost. The researcher reached a set of conclusions, the most important of which is that the application of cleaner production and measuring its costs contribute to improving the quality of the product by reducing the pollutants caused by the product and replacing materials harmful to the environment and human health with other materials that are less harmful and polluting the environment and reducing the rates of damage as a result of excluding activities that do not add value to the product or the customer. It led to reducing the cost of the product, meeting environmental requirements, increasing productivity, improving the reputation and image of the economic unit, and achieving a sustainable competitive advantage.